Paradoxes and partnerships: a study of knowledge exploration and explo itation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships b alance knowledge exploration and exploitation in contexts that are rif e with paradoxes. It draws on paradox theory to examine the partnershi p’s response to the explore-exploit relationship.